(untitled) ("Temas Sociais" Journal, 2025)
The protection of children and young people at risk constitutes a central axis of social policies and Social Work intervention, guided by the principle of the best interests of the child. Within the Portuguese child protection system, adoption is legally established as a permanent measure aimed at ensuring stability, secure attachment, and family integration; however, empirical evidence reveals its residual and often delayed application, following prolonged intervention trajectories and extended periods of residential care.This study aims to analyse the characteristics, challenges, and institutional trajectories associated with child protection processes involving children and young people with an adoption life project, monitored by a Court Technical Advisory Unit for Child Protection between 2024 and 2025. Methodologically, this is a descriptive mixed-methods study based on documentary analysis of 15 cases, combining qualitative content analysis with descriptive statistical analysis. The findings reveal prolonged intervention trajectories, frequently initiated at very early ages, marked by the persistence of risk factors—particularly neglect and parental dysfunction—and by the insufficiency of protective factors capable of promoting structural change in family conditions. The adoption life project is predominantly defined at a late stage, following the exhaustion of temporary measures, highlighting a significant tension between institutional timeframes and the child’s developmental time. This underscores the need for earlier assessments of parental capacity and timely decision-making oriented towards stability, secure attachment, and the holistic development of children.